2016
DOI: 10.1002/acn3.344
|View full text |Cite
|
Sign up to set email alerts
|

Archetypal NOTCH3 mutations frequent in public exome: implications for CADASIL

Abstract: ObjectiveTo determine the frequency of distinctive EGFr cysteine altering NOTCH3 mutations in the 60,706 exomes of the exome aggregation consortium (ExAC) database.MethodsExAC was queried for mutations distinctive for cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), namely mutations leading to a cysteine amino acid change in one of the 34 EGFr domains of NOTCH3. The genotype‐phenotype correlation predicted by the ExAC data was tested in an independent cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
156
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(161 citation statements)
references
References 36 publications
3
156
1
1
Order By: Relevance
“…In our Han Chinese cohort, which contained patients largely from eastern and southern China, the exon 11 was considered to be a “hot region,” in line with previous reports . Interestingly, a recent research based on ExAC database indicated that mutations causing CADASIL revealed an obvious distribution discrepancy and predominately located outside EGFR 1‐6 . Nevertheless, the mutation p.Arg607Cys, rather than p.Arg544Cys, ranked in the first place of the mutational spectrum in our subjects and occupied a ratio of nearly 20%.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In our Han Chinese cohort, which contained patients largely from eastern and southern China, the exon 11 was considered to be a “hot region,” in line with previous reports . Interestingly, a recent research based on ExAC database indicated that mutations causing CADASIL revealed an obvious distribution discrepancy and predominately located outside EGFR 1‐6 . Nevertheless, the mutation p.Arg607Cys, rather than p.Arg544Cys, ranked in the first place of the mutational spectrum in our subjects and occupied a ratio of nearly 20%.…”
Section: Discussionsupporting
confidence: 77%
“…9,10 Interestingly, a recent research based on ExAC database indicated that mutations causing CADASIL revealed an obvious distribution discrepancy and predominately located outside EGFR 1-6. 22 Nevertheless, the mutation p.Arg607Cys, rather than p.Arg544Cys, ranked in the first place of the mutational spectrum in our subjects and occupied a ratio of nearly 20%. scores.…”
Section: Discussionmentioning
confidence: 64%
“…In CADASIL, another dominantly‐inherited microvascular disorder of the brain, the burden of EGFr cysteine‐altering NOTCH3 variants in ExAC data—the type of variants known to be pathogenic or probably pathogenic in patients with CADASIL—was surprisingly 100‐fold higher than prevalence estimations of 2–5 p. 100,000 in epidemiological studies (Moreton, Razvi, Davidson, & Muir, ; Narayan, Gorman, Kalaria, Ford, & Chinnery, ; Razvi, Davidson, Bone, & Muir, ; Rutten et al, ). Observing a different distribution of these variants in the EGFr domains of NOTCH3 in ExAC compared to Dutch patients with CADASIL, the authors hypothesized that variants located in certain EGFr domains could have a milder effect leading to incomplete penetrance (Rutten et al, ). Conversely, PKD2 ‐Related Autosomal Dominant Polycystic Kidney Disease prevalence estimates was 0.63 (95%CI, 0.54–0.72) per 10,000 in the population of Brittany based on patients included in a cohort and 2.31 (95%CI, 1.10–3.51) per 10,000 in ExAC (Cornec‐Le Gall et al, ), revealing a much lower difference between the two estimations than for CADASIL.…”
Section: Discussionmentioning
confidence: 88%
“…Given the fact that (i) a significant proportion of PFBC patients do not exhibit neuropsychiatric symptoms; (ii) most of the symptomatic patients have a disease onset during adulthood; (iii) the few patients with symptomatic PFBC starting during childhood rarely present severe symptoms; and (iv) the disease penetrance is full when considering abnormal brain calcification as the major diagnostic criterion, it is reasonable to estimate a minimal prevalence from genomic data. The power of genome and exome sequencing in large populations gathered by ExAC makes this strategy now applicable through access to publicly available data (Appadurai et al, ; Cornec‐Le Gall et al, ; Minikel et al, ; Rutten et al, ; Sleat, Gedvilaite, Zhang, Lobel, & Xing, ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 500 families with the disease have been identified worldwide (the majority in Europe), with more than 230 unique mutations reported (Human Genetic Mutation Database website, www.hgmd.cf.ac.uk), but a clear genotype-phenotype correlation has still to emerge [196, 197]. Recently, mutations mapping to EGF repeats 1-6 have been associated with higher lesion load on MRI, possibly predisposing to a more severe form of the disease [198]. …”
Section: Cadasil (Cerebral Autosomal Dominant Arteriopathy With Subcomentioning
confidence: 99%